SORUS MORPHOLOGY IN FERNS OF THE Polypodiaceae AND Tectariaceae FAMILIES IN THE ATO WATU WATERFALL AREA, AMONGGEDO DISTRICT - Munir, Asmawati; Tenriawaru, Andi Besse; Sirniawan, Sirniawan (BRIN - Badan Riset dan Inovasi Nasional, 2025)
This study aims to determine the shape, color, and location of sori as well as the presence or absence of annulus in ferns (Pteridophyta) of the Polypodiaceae and Tectariaceae families in the Ato Watu Waterfall area, Amonggedo District, Konawe Regency, Southeast Sulawesi. The method used in this study was qualitative descriptive research with an exploratory method by exploring the Ato Watu Waterfall area to collect fern samples that had sori. The results of the study found six species of ferns in the Polypodiaceae family, including Drynaria quercifolia (L.), J, Lemmaphyllum accedens (Blume), Leptochilus henryi (Baker) X.C.Zhang, Microsorum membranifolium (R.Br.) Ching, Pyrrosia longifolia (Burm.fil.) C.V.Morton, Selliguea heterocarpa BI., FI. Jav (Mehltreter, et al., 2010: 835-838) And 5 species of ferns from the Tectriaceae family, including Tectaria angulata (Sw.) S. Chandra, Tectaria aurita (Sw.) S. Chandra, Tectaria barberi (Hook), Tectaria devaxa (Kze) Copel, Tectaria fuscipes (Wall. ex Bedd) C. Chr,. Of the 6 species of the Polypodiaceae family, 5 species of the Tectariaceae family found, they have different sorus characteristics, and each species has an annulus (Shin & Keun, 2017: 317-320).